2015
DOI: 10.1590/0034-7167.2015680117p
|View full text |Cite
|
Sign up to set email alerts
|

BANFISA e (IN)DICA-SUS na graduação em saúde: o lúdico e a construção de aprendizados

Abstract: Learning constructed by the students goes beyond the content of the subject; involve the active participation in group and creativity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 9 publications
1
10
0
7
Order By: Relevance
“…The profile of subjects, mostly young undergraduates of health care courses, contributed to contextualize the restlessness of a playful learning environment (13)(14) . The high estimate of intra-judge agreement measured by the kappa coefficient is based on previous research that confirmed the variables used in this study (14,21) . The low agreement of the judges in the subcategory of self-assessment is consistent with the literature, since this feature is not inherent in the ludic/playfulness component.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The profile of subjects, mostly young undergraduates of health care courses, contributed to contextualize the restlessness of a playful learning environment (13)(14) . The high estimate of intra-judge agreement measured by the kappa coefficient is based on previous research that confirmed the variables used in this study (14,21) . The low agreement of the judges in the subcategory of self-assessment is consistent with the literature, since this feature is not inherent in the ludic/playfulness component.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, the perspective of playfulness sought in this study focused on the disruptive and insubordinate character of the game -a trait necessary to train subjects of knowledge. So, the more players reinvent rules while immersed in ludic activities, the greater the chance of imaginative, restless and creative character being revealed -and these are the attributes of the ludic activity that are intended to be measured, aimed at the formation of autonomous individuals (9)(10)(11)(12)(13)(14)(15)(16)21,(25)(26) . The item I learn better when I express my creativity, although it had a successful consensus rating among the judges (CVIA/relevance 0.90 and CVIA/clarity 1.0), was excluded for having a low frequency of responses among the subjects who answered the open questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scope of action conceived in the game is essential and explains, partially, the pleasure that it evokes (9) . This concept of game is also operated in other experiences that use such strategies in education (6)(7)16) .…”
Section: Discussionmentioning
confidence: 99%
“…In order to face this reality, it is indispensable to seek pedagogic strategies that do not consider only the cognitive dimension of learning, but that stimulate the critical-reflexive and favor the interaction and the production of ways of subjectification (5) . In this perspective, the pedagogic strategy in game format manifests alternative with potential to establish a problem-based perspective, able to mobilize the players in their desires and experiences and favor the invention (6)(7)(8) , used here for the approach to the sexuality with adolescents.…”
Section: Introductionmentioning
confidence: 99%